The Testing of E-Module Flip-PDF Corporate to Support Learning: Study of Interests and Learning Outcomes - Erniwati, Erniwati; Hunaidah, Hunaidah; Nurhidayat, Rifki; Fayanto, Suritno (Universitas Pendidikan Ganesha, 2022)
ICT-based learning resources that are developed still need to be improved, especially in areas where learning facilities are lacking. It causes students difficulty in understanding the learning material. This study aims to develop an e-module on static fluid material based on corporate edition flip pdf software. The type of research used is Research and Development with the ADDIE method. The research object was class XI SMA, with a trial sample of 25 students. The research instrument consisted of validator sheets, teacher and student response questionnaires, and learning achievement test sheets. Data analysis techniques consist of descriptive analysis and hypothesis testing. The results showed that the static fluid physics learning e-module had a validity percentage of 89.95% (very good). The level of practicality of the static fluid physics learning e-module through the results of student responses is 87.42% (very good), and the teacher's response results are 86.25% (very good). The level of effectiveness of the learning e-module through students' learning interest obtains the medium category, and the increase in students' physics learning outcomes obtains the medium category. It indicates that the use of e-modules impacts interest and learning outcomes. The implication of this study is that learning e-modules are available in flip pdf corporate education that can be used by students and teachers as learning resources and can be accessed online online.